COLD TYRANNY AND THE DEMONIC NORTH OF EARLY MODERN ENGLAND - Cotterill, Anne. Link ([S.l.])
1 online resource
Keywords: The seventeenth and early eighteenth centuries were among the worst years of the Little Ice Age. This volume attends to English texts from this period to trace associations between wintry physical landscapes and an icy inner landscape of human cruelty and tyranny whose rigors promote the ultimate chill of rigor mortis. Sailors seeking a polar route to the East brought terrifying reports of northern icescapes, long popularly linked with the devil. Simultaneously, concerns about increasingly cold winters at home in Britain overlapped with increased scrutiny of kingship and the church and fear of tyranny from both. Such fears were reflected in ongoing struggles between king and Parliament during the period, leading to revolution and war. The binding power of ice and the power of northern winters to deface, kill, and bury life suggested the Fall's human parallel to winter: cold-hearted humans as tyrannical winters who deal in death.